2002
DOI: 10.1093/occmed/52.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C virus infection in barbers in the Sivas region of Turkey

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are among the most devastating health problems in the world, including Turkey. The route of transmission of HBV and HCV is mainly parenteral, a small number of epidemiological studies demonstrating that perinatal, sexual, household and occupational transmission occurs. Contact of a patient's blood or bodily fluids with non-intact skin is another mode of HBV and HCV transmission. Barbers in Turkey may often be exposed accidentally to the blood and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 6 publications
1
36
4
Order By: Relevance
“…In our country, HCV infection is lower than that of HBV [15]. In a study carried out in Sivas, Turkey, the HCV prevalence in 176 barbers and hairdressers was found to be 2.8%; and HBsAg positivity was 8.5% [16]. A study carried out by Özdemir et al in Sivas reported that HBsAg seropositivity was detected in 1.1% of barbers, hairdressers, and employees of beauty salons; anti-HBs -22.8%; anti-HCV -0.4% [17].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In our country, HCV infection is lower than that of HBV [15]. In a study carried out in Sivas, Turkey, the HCV prevalence in 176 barbers and hairdressers was found to be 2.8%; and HBsAg positivity was 8.5% [16]. A study carried out by Özdemir et al in Sivas reported that HBsAg seropositivity was detected in 1.1% of barbers, hairdressers, and employees of beauty salons; anti-HBs -22.8%; anti-HCV -0.4% [17].…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of HBV and HCV infections varies from country to country, and even from one region to another, based on environmental factors and host characteristics [16]. The area where our study took place was Izmir, a city in the west of Turkey and the 3rd biggest city in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In other similar seroepidemilogical studies conducted among barbers in Sivas region of Turkey and Huanshi of China, Candan et al and She et al reported that HBV and HCV seropositivity was elevated in traditional barbers compared to the general population (7,16). Our study showed that 0.8% of our subjects were HBs Ag carriers and there was a total of 6.6% HBV seropostivity.…”
Section: Discussionmentioning
confidence: 79%
“…The prevalence of HBV and HCV is known to differ across countries and may also differ based on the individual characteristics and conditional factors (7,8). Hepatitis B virus and HCV infections are common causes of occupational blood-borne diseases that can be transmitted between barbers and their clients and frequently lead to a chronic asymptomatic carrier condition for a long time before the development of severe end-stage liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation